The Effect of Green Banking on the Decision to Become an Islamic Bank Customer - Citra Septiyani; Fetria Eka Yudiana (Jurnal Riset Perbankan Syariah, 2026)
Climate change and increasing public concern for environmental sustainability have encouraged Islamic banking institutions to adopt green banking principles as part of their environmental and social responsibility. Within the Islamic banking context, green banking reflects not only sustainability commitments but also the integration of Islamic ethical values and social welfare. This study examines the effects of green brand image, environmental awareness, and value congruence on customers’ decisions to become clients of Bank Syariah Indonesia (BSI). A quantitative approach was employed with a sample of 170 Generation Z and millennial BSI customers in Indonesia. Data were collected through questionnaires and analyzed using multiple linear regression. The findings reveal that green brand image, environmental awareness, and value congruence have positive and significant effects on customer decisions, both partially and simultaneously. These results strengthen the theoretical understanding of green banking adoption in Islamic banking by highlighting the role of sustainability-oriented branding, environmental values, and value alignment in shaping customer decisions. The study implies that Islamic banks need to reinforce sustainability strategies while integrating Sharia values to enhance customer preference and competitiveness.